Among Video-Based Learning, Web-Based Learning and EFL Students’ Mastery of Conditional Sentences: A Study of Senior High School Level - Mangundap, Juniva J.; Rorintulus, Olga A.; Wuntu, Ceisy N. (English Education Department, 2025)
This research explored the impact of Video-Based Learning (VBL) and Web-Based Learning (WBL) on enhancing the understanding of conditional sentences (Types 1, 2, and 3) among Grade 10 students at SMA UNKLAB Airmadidi. Employing a quasi-experimental design, 60 students were assigned to two groups: one received instruction via VBL, while the other was taught using WBL. Pre-test and post-test results were examined using IBM SPSS Version 26, with both paired-sample and independent-sample t-tests applied. The paired-sample t-test indicated notable improvement in both groups. The average score for the VBL group rose from 33.60 to 77.87, and for the WBL group from 33.20 to 59.73. The independent-sample t-test yielded a Sig. (2-tailed) value of 0.001, signifying a statistically significant difference between the groups. While both approaches were effective, VBL demonstrated a more substantial effect on students' grammar proficiency. Additionally, analysis showed no significant difference in performance based on gender, suggesting that both teaching methods were equally effective for male and female students. Overall, the findings underscore the advantages of incorporating digital media in grammar instruction, with VBL particularly enhancing student engagement and understanding of complex grammar topics. This study affirms the value of multimedia in English teaching and highlights the potential of visual and interactive content to boost learner motivation and success.